PERLINDUNGAN HUKUM PENGETAHUAN TRADISIONAL PADA AYAMNAPINADAR SEBAGAI INSTRUMEN PELESTARIAN BUDAYA LOKAL DAN PENINGKATAN EKONOMI MASYARAKAT BATAK TOBA - Philip Marchello Hasonangan Sinaga; Parlaungan Gabriel siahaan; Roslin Naiborhu; Robintang Lumban Batu; Jessi Aprillia Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Traditional knowledge is an important part of the cultural identity of indigenous communities, passed down through generations and serving social, spiritual, and economic functions. One manifestation of this is evident in Toba Batak cuisine, namely Ayam Napinadar, a traditional dish containing symbolic value and deep cultural meaning. For the Toba Batak people, Ayam Napinadar not only plays a role in traditional ceremonies but also serves as a symbol of respect, togetherness, and a source of economic strengthening for the community. However, modernization and commercialization of culinary arts pose challenges such as declining interest from the younger generation, the loss of traditional processing techniques, and risks triggered by outsiders who do not understand its philosophical value. Furthermore, legal protection for traditional knowledge in Indonesia is not optimal because existing regulations do not provide a specific mechanism to protect traditional culinary traditions communally. This study uses a qualitative descriptive method to describe the conservation practices, processing techniques, cultural meaning, and economic potential of Ayam Napinadar. Data were collected through direct observation at the Kepala Kakap Restaurant and in-depth interviews with the owner and employees who understand the production process. Additional documentation in the form of field notes and photographs was also used to strengthen the findings. The analysis was conducted through a process of data reduction, presentation, and verification using source triangulation. The results indicate that the preservation of Ayam Napinadar still relies on oral transmission and is carried out directly without formal documentation. Legal protection is also inadequate, making this dish vulnerable to shifting meanings and exploitation. Nevertheless, Ayam Napinadar has significant economic potential through culinary tourism and the development of MSMEs. Therefore, special regulations, systematic documentation, and community empowerment are needed to prevent cultural poverty while boosting the local economy.